Numerical study of an experimental high-intensity prescribed fire across Corsican Genista salzmannii vegetation. (July 2022) - Fayad, Jacky; Rossi, Lucile; Frangieh, Nicolas; Awad, Carmen; Accary, Gilbert; Chatelon, François-Joseph; Morandini, Frédéric; Marcelli, Thierry; Cancellieri, Valérie; Cancellieri, Dominique; Morvan, Dominique; Pieri, Antoine; et al.
Abstract: This paper reported a high intensity experimental fire conducted during a field-scale experiment on a steep sloped terrain (28°) as part of a winter prescribed burns campaign managed by the local firefighter service in the north-western region of Corsica. The rate of spread (ROS) of fire, measured using UAV cameras (thermal and visible), was evaluated at 0.45 m/s. The experiment was numerically reproduced using a completely physical 2D model, namely FireStar2D, and the comparison with the experimental measurements mainly concerned the fire ROS and the heat fluxes received by three distant targets placed at the end of the plot. The results analysis shows that the considered fire has a wind-driven regime of propagation with a fire intensity higher than 7 MW/m. The numerical results are in fairly good agreement with the experimental measurements, within 11% difference for the ROS and 5% for the heat fluxes, validating consequently the relevance of the numerical approach to tackle such high-intensity wildfires. Despite the unfavorable wind and humidity conditions for fire propagation (U = 1.67 m/s and RH = 82%), this experiment confirms that such fire can exhibit a dangerous behavior due to the steep slope of the terrain.